From Pole to Pole a Thermal Challenge - Radomski, M. W.; Buguet, A. (2002)
The issues of thermal physiology, protection, modeling, survival, and injury have been addressed in thousands of publications over the decades, and the topic of thermal protection and survival has been the subject of several NATO DRG and AGARD symposia. Therefore, rather than review the current state of the art of the field which is the subject of the many papers that will be presented at this Symposium, this paper re-examines some of the pioneer work in cold physiology that has laid the foundations of our current understanding as to how humans have adapted to severe cold climates, often without modem technology or clothing. Scholander, Hammel, Elsner, Andersen, and Hart are some of the scientific pioneers that have provided evidence from field trials that a variety of physiological adaptations can develop in the human species exposed to different climatic extremes ranging from one Pole to the other Pole. From these classical field studies, several different types of cold acclimatization of native races were identified. This paper reviews how some of these acclimatizations can be or have been applied to modern man. In conclusion, it appears that a rapid technique using intermittent exposure to severe cold for inducing cold adaptation or cold habituation does exist and does induce beneficial effects in soldiers required to subsequently perform and sleep under arctic conditions. It appears to be a hypothermic type of adaptation and eliminates the negative effects of cold diuresis. Furthermore, this technique appears to persist over a significant period of time even in a temperature environment making it even more of a desirable military technique. One sees a shift of the shivering threshold to a lower temperature, a shorter period of adaptation, and an increase in cold tolerance. It appears to be more akin to the type of adaptation demonstrated by the Australian aborigine and Kalahari bushman, that is, an Insulative Acclimatization. 8 Oct 2001 to 10 Oct 2001, "The original document contains color images" Papers presented at the RTO Human Factors and Medicine Panel (HFM) Symposium held in Dresden, Germany, 8-10 Oct 2001, pKN1-1/KN1-19. This article is from ADA403853 Blowing Hot and Cold: Protecting Against Climatic Extremes (Souffler le chaud et le froid: comment se proteger contre les conditions climstiques extremes)